2015
DOI: 10.1002/jso.23869
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy does not adversely impact outcome following post‐incisional hernia repair with biomaterial mesh

Abstract: Background: Patients receiving chemotherapy are at increased risk for developing recurrent or post-incisional hernias (PIH). Biological materials are an alternative to synthetic mesh in contaminated fields. The impact of chemotherapy on biomaterial tissue ingrowth and integration has not been well studied. Methods: From 2008 to 2011 patients who underwent PIH repair with biomaterial mesh (Biodesign 1 ) were selected. Patients were divided into two groups: those receiving chemotherapy (CT) and those not receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Immunosuppression due to chemotherapeutic agents or malignancy itself can not only increase the infection risk but may also result in higher recurrence rates because of impaired inflammatory response to tissue integration and scar formation. A retrospective series revealed that surgical site occurrence rates after incisional hernia repair with biological mesh did not differ between the groups receiving or not receiving chemotherapy (187). However, some problems might arise when synthetic meshes are used instead of expensive biological meshes.…”
Section: Discussionmentioning
confidence: 99%
“…Immunosuppression due to chemotherapeutic agents or malignancy itself can not only increase the infection risk but may also result in higher recurrence rates because of impaired inflammatory response to tissue integration and scar formation. A retrospective series revealed that surgical site occurrence rates after incisional hernia repair with biological mesh did not differ between the groups receiving or not receiving chemotherapy (187). However, some problems might arise when synthetic meshes are used instead of expensive biological meshes.…”
Section: Discussionmentioning
confidence: 99%
“…The recent diffusion of biologic materials-based meshes has lowered infection rates and overall complication rates in high-risk patients [ 3 , 11 ]. For these reasons, we performed this retrospective study to evaluate the usefulness and safety of the use of BIOMESH in high-risk patients who underwent chemotherapy in a short time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Post-incisional ventral hernia (VH) is a common complication after abdominal surgery reaching an incidence that ranges between 2 and 20% according to the literature [ 1 3 ]. Several factors are related with its presentation depending on both technical aspects and patient characteristics; type of abdominal incision, suture materials, surgical technique, and type of mesh used to repair the defect are important technical factors to consider as well as advanced age, high BMI, post-operative septic complications and corticosteroid treatment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations